Analysis of life cycle assessment of food/energy/waste systems and development and analysis of microalgae cultivation/wastewater treatment inclusive system - Armstrong, Kristina Ochsner, author; Bradley, Thomas H., advisor; De Long, Susan, committee member; Marchese, Anthony, committee member (Colorado State University. Libraries, 2013)
Across the world, crises in food, energy, land and water resources, as well as waste and greenhouse gas accumulation are inspiring research into the interactions among these environmental pressures. In the food/energy/waste problem set, most of the research is focused on describing the antagonistic relationships between food, energy and waste; these relationships are often analyzed with life cycle assessment (LCA). These analyses often include reporting of metrics of environmental performance with few functional units, often focusing on energy use, productivity and environmental impact while neglecting water use, food nutrition and safety. Additionally, they are often attributional studies with small scope which report location-specific parameters only. This thesis puts forth a series of recommendations to amend the current practice of LCA to combat these limitations and then utilizes these suggestions to analyze a synergistic food/waste/energy system. As an example analysis, this thesis describes the effect of combining wastewater treatment and microalgae cultivation on the productivity and scalability of the synergistic system. To ameliorate the high nutrient and water demands of microalgae cultivation, many studies suggest that microalgae be cultivated in wastewater so as to achieve large scale and low environmental costs. While cultivation studies have found this to be true, none explore the viability of the substitution in terms of productivity and scale-up. The results of this study suggest that while the integrated system may be suitable for low-intensity microalgae cultivation, for freshwater microalgae species or wastewater treatment it is not suitable for high intensity salt water microalgae cultivation. This study shows that the integration could result in reduced lipid content, high wastewater requirements, no greenhouse gas emissions benefit and only a small energy benefit.
Keywords: biofuels; wastewater; microalgae; life cycle analysis; LCA